Analyzing The Influence of Oriental Elements on Luxury Brands - Chen, Jiachun (Transactions on Economics, Business and Management Research, 2024)
With the development of globalization and the deepening of cultural integration, oriental elements occupy an increasingly important position in the world fashion and luxury goods industry. The purpose of this paper is to explore how oriental elements affect luxury brands. In this context, Chanel Coromandel’s high-end jewelry series shows the perfect integration of eastern and western aesthetics with the design of oriental elements, which has become a typical case of exploration. This paper uses the theories of cultural semiotics, brand differentiation, and cross-cultural brand management to investigate and promote the cultural value of luxury goods by incorporating oriental elements. This paper examines how to differentiate luxury goods in the market by incorporating oriental elements and enhancing the image of luxury brands. The paper recommends collaborating with traditional Chinese intangible technology, adopting China’s traditional philosophy, and focusing on the exploration and inheritance of jewelry technology. It also reveals the influence of oriental elements on luxury brands, providing guidance for cross-cultural marketing strategies and the strategic deployment of luxury brands in China and other Asian markets.